RENCANA STRATEGIS SISTEM INFORMASI/TEKNOLOGI INFORMASI MENGGUNAKAN ENTERPRISE ARCHITECTURE PLANNING (EAP) DENGAN ZACHMAN FRAMEWORK - Sri Murni (Jurnal Khatulistiwa Informatika, 2015)
One of phenomenon that is around the world and developed quickly is developing through some penetrations in technology information area. The purpose in application technology information by instance of government is to improve instance skill government in the process, manage, distribute and distribute information and public service. Based on the President’s instruction number 3 in a year 2003 about e-government, so it is need to planning the IS strategy and IT to support business activity in the government. Dinas Pekerjaan Umum Provinsi Kalimantan Barat is one of publics that has a task and function were doing the business of local government in general working area. The complex activity in the instance give an effect in coordination between a part and the area walking well. The planning program of the process often overed the limited time, sometimes the working project between a part lame overlap each other and budget project cost doubled. It is cause of there is no strategy planning IS/IT for Dinas PU Provinsi Kalimantan Barat. One of the approaches to makes strategy planning IS and IT is Enterprise Architecture Planning (EAP). EAP is a method to develop an information arsitecture. One of frameworks to developing EAP is Zachman Framework. The result that whises from the usage EAP through framework Zachman can made a strategy planning and IS/IT arsitecture that needed to help and support the business process in Dinas PU Provinsi Kalimantan Barat.Keyword: The Usage of EAP, IS/IT Strategy Planning, Zachman Framework